P Pengaruh Kombinasi Basis Karbopol 940 dan HPMC Terhadap Evaluasi Dan Stabilitas Sediaan Spray Gel Ekstrak Daun Sembung (Blume balsamifera (L.)) - Uzma, Nor Syafa'atul; Budi, Setia; Rahmadani, Rahmadani (LPPM Universitas Sari Mulia, 2024)
Background: Sembung leaf extract was made into spray gel preparations, with various concentrations of carbopol 940 and HPMC. Spray gel was chosen because it has the advantage of being practical to use, relatively low contamination of microorganisms, easier to dry and easy to wash. Objective: To determine the effect of varying concentrations of Carbopol 940 and HPMC on the physical evaluation and stability of Sembung leaf extract spray gel (Blumea Balsamifera (L.)). Methods: The method used is laboratory experimental with one shot case study. Sembung extract was formulated into 4 spray gel formulations with various concentrations of carbopol 940 and HPMC respectively (0.2:0.5);(0.4:0.6);(0.6:0.7) and (0 ,8:0,4). Then a stability test was carried out using the cycling test method for 12 days for 6 cycles by evaluating before and after the cycling test, the evaluation included organoleptic tests, homogeneity, pH, viscosity, spreadability and spraying pattern, dry time and adherence resistance. Results: Organoleptic test results showed differences in color and consistency, homogeneity test obtained homogeneous preparations, pH test and viscosity of the formula decreased, spreadability test and good spraying pattern were formula III and IV, dry time test of all preparations was good, good adhesion resistance test are formulas III and IV. Conclusion: Variations in the concentration of Carbopol 940 and HPMC have an effect on the preparation before and after the stability test. Good preparations were found in formulas III and IV with concentrations of carbopol 940 and HPMC (0.6:0.7) and (0.8:0.4).